Penerapan Metode Diskusi dan Eksperimen Kelompok dalam Pembelajaran Besaran dan Satuan untuk Meningkatkan Pemahaman Konsep Siswa Kelas X (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
This study aims to analyze the effectiveness of applying group discussion and experiment methods in improving students’ conceptual understanding of the topic of Physical Quantities and Units among tenth-grade students at SMA Negeri 7 Kota Jambi. The research employed a quantitative approach with a quasi-experimental design using the Pretest–Posttest Control Group Design. The sample consisted of two classes: the experimental class, which received learning through group discussions and hands-on experiments, and the control class, which was taught using conventional lecture-based instruction. The research instruments included achievement tests and student activity observation sheets. Data were collected through pretests administered before the treatment and posttests administered after the learning process. The findings revealed a significant improvement in the experimental class compared to the control class. Students in the experimental class demonstrated higher learning activity, better collaboration skills, and stronger conceptual understanding of fundamental and derived quantities as well as SI units. Statistical analysis using the paired sample t-test also indicated a significant difference between the pretest and posttest scores in the experimental class. Thus, it can be concluded that the combination of discussion and group experiment methods is effective in enhancing students’ conceptual understanding in basic Physics learning.